2012
DOI: 10.3354/meps09877
|View full text |Cite
|
Sign up to set email alerts
|

Continuous acoustic studies of overwintering sprat Sprattus sprattus reveal flexible behavior

Abstract: The clupeid fish Sprattus sprattus was studied in a 150 m deep Norwegian fjord throughout an entire overwintering period during which the fjord froze over and a major water renewal occurred. A bottom-mounted (upward-facing) echosounder provided continuous highresolution data and enabled studies of swimming speed and behavior of individual sprat in addition to population behavior. The continuous acoustic studies were supplemented with intermittent field campaigns. The sprat displayed different behavioral modes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 45 publications
5
15
0
Order By: Relevance
“…Our trawl catches identified that the dielly migrating scattering layers consisted of the krill M. norvegica and clupeids, in accordance with results from many years of sampling and acoustic studies in this location (Kaartvedt et al 2009;Klevjer and Kaartvedt 2011;Solberg et al 2012). The diel pattern of sedimentation was initiated at the onset of the spring bloom, and it abated at the culmination of the bloom.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our trawl catches identified that the dielly migrating scattering layers consisted of the krill M. norvegica and clupeids, in accordance with results from many years of sampling and acoustic studies in this location (Kaartvedt et al 2009;Klevjer and Kaartvedt 2011;Solberg et al 2012). The diel pattern of sedimentation was initiated at the onset of the spring bloom, and it abated at the culmination of the bloom.…”
Section: Discussionsupporting
confidence: 87%
“…This study revealed regular diel pulses of sedimenting particles that were associated with the arrival of krill (M. norvegica) in upper waters at night and that terminated subsequent to the return of krill to their daytime habitat in the morning. Our trawl catches identified that the dielly migrating scattering layers consisted of the krill M. norvegica and clupeids, in accordance with results from many years of sampling and acoustic studies in this location (Kaartvedt et al 2009;Klevjer and Kaartvedt 2011;Solberg et al 2012). The diel pattern of sedimentation was initiated at the onset of the spring bloom, and it abated at the culmination of the bloom.…”
Section: Discussionsupporting
confidence: 87%
“…(Solberg et al ., 2012) reporting on the individual swimming behaviour of krill in near bottom waters and the overwintering strategies of the clupeid fish sprat, respectively. These studies also provide information on environmental conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The differences in the spatial structure between regions were confirmed with the geostatistic analysis, showing that both the spatial variance and the correlation distance (range) were smaller in the Aysén region. It is probable that the patterns of distributions of the austral sardine could vary as a function of environmental conditions, including the geography, such have been described for the Sprattus sprattus in the innermost part of the Oslofjord [21].…”
Section: Discussionmentioning
confidence: 98%